Contribution to the translation and validation of the Adapted Illness Intrusiveness Ratings Scale for the Portuguese context - Luz, Elisabete (2017)
Background: The Adapted Illness Intrusiveness Ratings Scale was adapted and validated for the Portuguese context. Following the process of translation, its psychometric properties were measured with the purpose of assessing its validity and reliability. Objectives: Translation and validation of the scale. Methodology: The instrument was applied to a convenience sample of 271 people with chronic illness, aged 18-65 years, and living in Lisbon. An exploratory factor analysis was performed to assess its psychometric properties. The model proposed by the author was confirmed through confirmatory factor analysis. Results: The factor analysis with Varimax rotation revealed three dimensions (Instrumental Activities, Intimacy, Relationships and Personal Development), which explained 73.24% of total variance. The scale showed an overall internal consistency of 0.92. Conclusion: The scale proved to be a reliable, valid, and useful tool to measure the perceived interference of chronic disease in people’s lives.